The cost of private transportation in the Netherlands, 1992-1999 - Ben Bode; Jan Van Dalen (European Central Bank (ECB), 2002)
User-cost indexes provide important information about the welfare implications of durable goods purchases. In this paper indexes for the cost of private transportation are developed, based on the costs associated with using new passenger cars sold in 1992-1999, in the Netherlands. The paper examines the existence of differences between car model based user-cost indexes and CPI based indexes. Use is made of information about prices and technical characteristics of about 7,000 car models. In addition, data on user costs are used. The results show that total annual user costs have increased about 4.8% over the observation period vs. 10.6% according to the CPI based index. Fixed costs have increased about 9% both for the car model and the CPI based index. Operating costs have decreased more than 3% according to the car model based index, whereas an increase of more than 13% is observed for the CPI based index.
Keywords: C43; D12; E31; 330